1999
DOI: 10.1159/000022067
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes on Glucose Transport and Utilization of Human Erythrocytes: Effect of Oxidative Stress

Abstract: Background: Normal aging is associated with an impairment in glucose homeostasis. Methods: In order to investigate the effect of aging on glucose transport and utilization in erythrocytes, the transport and utilization of glucose were measured in erythrocytes from 10 young (mean age 26 ± 3 years) and 10 elderly (mean age 70 ± 7 years) healthy individuals. In addition, the glucose transport and utilization were also measured in the presence of cumene hydroperoxide (CumOOH), a toxic organic hydroperoxide that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…However, the changes of L-cysteine transport capacity during storage and its influence on the antioxidant capacity of erythrocytes remains unclear. A previous study by M Güven demonstrated that oxidative stress significantly decreased in glucose transport and utilization efficiency [19]. Herein, we assumed that oxidant stress leads to decreased levels of glucose metabolism and ATP production in RBCs during storage, which may further induce the inhibition of GSH synthesis in erythrocytes due to the dysfunction of ATP-dependent L-cysteine transport.…”
Section: Introductionmentioning
confidence: 86%
“…However, the changes of L-cysteine transport capacity during storage and its influence on the antioxidant capacity of erythrocytes remains unclear. A previous study by M Güven demonstrated that oxidative stress significantly decreased in glucose transport and utilization efficiency [19]. Herein, we assumed that oxidant stress leads to decreased levels of glucose metabolism and ATP production in RBCs during storage, which may further induce the inhibition of GSH synthesis in erythrocytes due to the dysfunction of ATP-dependent L-cysteine transport.…”
Section: Introductionmentioning
confidence: 86%
“…are a feasible biological system to study in aging-related investigations, because unsaturated lipids in the cell membrane, amino acids, and DNA nucleotides represent specific target for free radical damage. 1,2 Moreover, recent studies point out the role of oxidative damage to biomembranes in a number of chronic inflammatory and degenerative diseases. Indeed, despite the fact that no overt changes of membrane components have been reported in erythrocytes (RBC) with advancing age, 3 peroxinitrite anion-related damages to platelets and RBC have been implicated in age-related neu-rodegenerative disease.…”
Section: Introduction E Rythrocytes and Erythrocyte Membranesmentioning
confidence: 99%
“…Replacing SB with MVPA/LPA tended to have a larger effect on reducing the glucose metabolism markers in young adults and middle‐aged people compared with old people. The reason may be that normal aging is associated with an impairment in glucose homeostasis, and the levels of glucose transport and utilization in old people may be lower as compared with young and middle‐aged people (Güven et al, 1999). At present, the World Health Organization's physical activity guidelines provide recommendations for adults as one group, and there are still insufficient physical activity recommendations for adults of specific age groups and genders (Physical Activity Guidelines Advisory Committee, 2018).…”
Section: Discussionmentioning
confidence: 99%